The Role of Multimedia in General and Economic Vocational Training - Sternerné Végh, Ágnes (Acta Agraria Debreceniensis, 2003)
The subject of my study is the methodological question of one of the topics of operation research as an application field of mathematics. The mathematics and operation research team of our institute aims to provide up to date knowledge to our students of both regular and distance education courses. Each topic has been allotted to a different teacher, thus my responsibilities include Networks and their economic application, and my ambition is to achieve increasingly good results teaching this subject. The distance education course of our college provides the opportunity to try a wide range of methodological methods.